(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
هدف البحث إلى تعرّف مشكلات إعداد الخطة التربوية بوزارة التربية، وآراء العاملين في التخطيط التربوي حول مشكلات إعداد الخطة التربوية وفقاً لمتغيرات (الجنس، المؤهل العلمي، عدد سنوات الخبرة).اعتمد البحث المنهج الوصفي التحليلي باستخدام استبانة محكّمة، تضمنت أربعة محاور وزّعت على عينة شملت العاملين في التخطيط التربوي بوزارة التربية تم اختيارهم بالطريقة القصدية نظراً لصغر حجم العينة، وقوامها (75) عامل وعاملة، وقد توصلت نتائج البحث إلى ما يلي: 1 وجود فروق دالة إحصائياً عند مستوى دلالة (0.05=α) بين متوسطات إجابات أفراد عينة الدراسة الذكور و متوسطات إجابات أفراد عينة الدراسة الإناث حول درجة مشكلات إعداد الخطة التربوية على الدرجة الكلية للاستبانة لصالح الإناث. 2 وجود فروق دالة إحصائياً عند مستوى دلالة (0.05=α) بين المتوسطات الحسابية لاستجابات أفراد عينة الدراسة باختلاف مؤهلاتهم العلمية لصالح المؤهل العلمي أكثر من دبلوم. 3 وجود فروق دالة إحصائياً عند مستوى دلالة (0.05=α) بين المتوسطات الحسابية لاستجابات أفراد عينة الدراسة باختلاف سنوات الخبرة لصالح الأفراد الذين لديهم خبرة من (11- 15). The aim of this research is to identify the problems of the preparation of the Educational Plan by the Ministry of Education, and the views of workers in educational planning on the problems of preparing the educational plan according to the variables of gender, qualification, and years of experience. The research adopted a descriptive analytical method using a questionnaire court, which included four axes, and was distributed to a sample of workers of educational planning in the Ministry of Education. The sample was selected in an intentional way because of the small sample number of workers (75). The hypotheses are tested at the 0.05 level of significance: Results show the following: • There are statistically significant mean score differences between males and females about the degree of the problems in preparing the educational plan for females. • There are statistically significant mean score differences in answers of respondents related to their qualifications, differences in favour of those with higher qualification (diploma and above). There are statistically significant mean score differences based on experience in favour of those with 11-15 years experience.